1989
DOI: 10.1002/j.0022-0337.1989.53.11.tb02366.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the economic evaluation of community water fluoridation

Abstract: Community water fluoridation has long been recognized as an effective public health intervention in the prevention of dental caries. The recently documented secular decline in dental caries, however, presents for policy makers the challenge of appropriately allocating limited health care resources between a variety of health care programs. Appropriate economic assessment of these alternatives becomes critical for rational distribution of such resources. Cost‐benefit and cost‐effectiveness analyses are techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…Our systematic search for economic information identified 27 candidate studies (see Appendix A). 39,46, Of these,18 were excluded for the following reasons: they (1) were not primary studies (10 studies 39,52,60,63,65,70,71,73,75,76 ); (2) did not report sufficient cost data (6 studies [55][56][57]62,63,69 ); (3) compared costs between low fluoride and optimal fluoride exposure groups without controlling for confounding factors (1 study 54 ); or (4) reported the cost of removing fluoride from water with extremely high levels of natural fluoride (1 study 74 ). The remaining 9 studies were considered qualifying studies from which we present the following summary findings.…”
Section: # Of Measures Median Change Rangementioning
confidence: 99%
“…Our systematic search for economic information identified 27 candidate studies (see Appendix A). 39,46, Of these,18 were excluded for the following reasons: they (1) were not primary studies (10 studies 39,52,60,63,65,70,71,73,75,76 ); (2) did not report sufficient cost data (6 studies [55][56][57]62,63,69 ); (3) compared costs between low fluoride and optimal fluoride exposure groups without controlling for confounding factors (1 study 54 ); or (4) reported the cost of removing fluoride from water with extremely high levels of natural fluoride (1 study 74 ). The remaining 9 studies were considered qualifying studies from which we present the following summary findings.…”
Section: # Of Measures Median Change Rangementioning
confidence: 99%
“…Thirty-four articles were selected for full text review. Of these, five were excluded due to being cost studies [18][19][20][21][22]; two due to being review articles [23,24]; two did not have comparators [25,26] and two articles were in French [27,28]. In addition, three articles were identified by hand search and other online sources.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in applied force from 0.6 to 5.0 N led to a 47% decrease in plaque deposition in patients with fixed appliances. 11 However, it was previously thought that brushing orthodontic fixed appliance brackets with a powered brush might be too aggressive,…”
Section: Toothbrushing Technique For Orthodontic Patientsmentioning
confidence: 99%